In Search of the Hill’s Monsters: Children in Front of the Face of Evil - Grammeni-Eleni Pourni (ΚΕΙΜΕΝΑ για την έρευνα, τη θεωρία, την κριτική και τη διδακτική της Παιδικής και Εφηβικής Λογοτεχνίας, 2023)
It is well known that history repeats itself. Greece faced multiple economic, political and social problems in the past decade. Prominent Greek children’s and adolescents’ writer Loty Petrovits-Androutsopoulou foresaw the danger of the neo-Nazi’s movement revival almost twenty years ago. In her teen novel, The Monsters of the Hill (2002), the writer describes the adventurous story of two teenage girls trying to help a little immigrant boy from Africa. At the same time, she refers to the parallel story of two German-Greek teenagers living in Germany whom German neo-Nazis have attacked. According to research, racist and extreme right or left movements and groups are present in times of social and economic crisis and in everyday life during prosperity and growth. They need to belong somewhere; Parents’ negligence towards children and the simple and straight way of thinking that these movements follow attract young people and consist some of their main characteristics. The danger of them reappearing is always present, so everybody must stay alert and open their eyes. The two young heroines prove with their stance that protecting vulnerable and sensitive social groups is everyone’s obligation, from children to adults and extends to state authorities. Keywords: Loty Petrovits-Androutsopoulou, Neo-Nazis, immigrants, racism.